When bad things happen to rotten people: indifference to incidental harms in the criminal justice system - De Vel-Palumbo, Melissa (Psychology, crime & law, 2023)
When we see others in pain, sympathy is often our instinctive and expected response. Yet in some cases, we may be indifferent to—and even take pleasure in—the suffering of others. Particularly, the public has historically expressed apathy toward and even endorsement of incidental harms experienced by those in the criminal justice system (i.e. catching a disease or experiencing abuse or neglect in custody). In this paper, we propose a new conceptual framework for understanding these views. We contend that people make character-based judgments to justify the incidental suffering of people who have committed crimes. By being in prison, or by having committed a crime in the past, one may be viewed as fundamentally distinct from other citizens—now categorized as a fundamentally “rotten” person who deserves any further suffering they might experience. We explore the nature of incidental harms suffered by those in the criminal justice system, as well as identify potential psychological and cognitive mechanisms that may underlie public indifference to such suffering, including psychological essentialism and immanent justice reasoning. Finally, we outline the legal and social implications of such views, and ultimately, propose ways in which future research might advance knowledge about this phenomenon.